Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.